THE STRUGGLES OF WOMEN TOWARD GENDER INEQUALITY PORTRAYED IN ENOLA HOLMES: THE CASE OF THE MISSING MARQUESS NOVEL BY NANCY SPRINGER - Julia Dianto; Singgih Daru Kuncara (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
Gender inequality is a phenomenon that has never been separated from everyday life in the past until now. Women are considered as weak, helpless, and inferior to men, giving rise to gender inequality in everyday life. Gender inequality gives rise to the struggle of women to get equality with men in various fields of everyday life. This study aims to identify gender inequality experienced by female characters in Enola Holmes: The Case of the Missing Marquess Novel by Nancy Springer and analyzed how women struggle in dealing with gender inequality that occurs by using Judith Lorber's theory regarding gender inequality and women's struggles. This research is qualitative research conducted with a feminist approach. The data source used in this study is Enola Holmes: The Case of the Missing Marquess Novel by Nancy Springer. The data collected was in the form of dialogues and narrations that contain gender inequality and women's struggles. Based on data analysis, the researcher found gender inequality and women’s struggle that occurred in various fields, such as educational fields, economic fields, marriage life, sexual exploitation and violence, and political fields through several characters in the novel, such as Enola Holmes, Eudoria Holmes, and other female characters. The results of this study showed how the forms of gender inequality experienced by women have led to women's struggles to achieve equality, which will also have an effect on gender inequality and women's struggles in the future.